Official Methods of Analysis: of AOAC INTERNATIONAL (OMA) - Latimer, George W.
The Official Methods of Analysis of AOAC INTERNATIONAL (OMA) is an international source of methods and voluntary consensus standards, with many countries and international organizations contributing their expertise. OMA is the most comprehensive and reliable collection of chemical and microbiological methods available in the world and are contained in many of the Codex food standards.